Eficácia do treinamento assertivo na depressão - Simões Junior, Volney Varzim (1986)
Assertion training has become an increasingly popular treatment technique and has been used with a wide variety of interpersonal problems. However, 'little has been done to evaluate its effectiveness on depression. In this work an attempt was made to show the importance of the technique in alleviating neurotic depression. A non-analogue study of the effects of assertion training on depression, using single-case experimental design strategie, was tried. To a certain extent results supported the effectiveness of treatment. Some considerations were given to recent behavioral approaches concerning depression and a small, historical approach relate to the development of assertive training was presented as well. It was concluded that if the loss of response-contingent reinforcement is the basis for depressed behavior, itis possible to alleviate depression by restoring and increasing the incidence of positive reinforcement using assertive training, even if we subscribe to the idea that lack of control over environmental events is ultimately at the root of depressed behavior.